The Impact of Proton Pump Inhibitors on the Efficacy of Immune Checkpoint Inhibitor Combinations in Patients with HBV-Associated Advanced Hepatocellular Carcinoma - Wang N; Xu Y; Yang G; Chen H; Wang X; Fu J; Li L; Pan X (Journal of Hepatocellular Carcinoma, 2024)
Ningning Wang, Yuanyuan Xu, Guangde Yang, He Chen, Xia Wang, Juanjuan Fu, Li Li, Xiucheng Pan Department of Infectious Disease, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of ChinaCorrespondence: Xiucheng Pan, Email xzpxc68@126.comPurpose: There is limited research on whether Proton Pump Inhibitors (PPIs) will affect the efficacy of immune checkpoint inhibitors (ICIs) in treating hepatocellular carcinoma (HCC).This study aimed to determine whether PPIs affect the survival outcomes of patients with HBV-associated advanced HCC receiving combination therapy based on ICIs.Methods: We retrospectively analyzed patients with hepatitis B virus (HBV)-associated advanced HCC who underwent ICIs combination therapy from January 1, 2020, to December 30, 2022. Patients were stratified into PPI and non-PPI groups based on whether they received PPI treatment within 30 days before or after ICIs therapy. Patients’ survival and the risk of PPI-associated mortality was assessed. Adverse events were also evaluated.Results: A total of 183 patients with HBV-associated HCC treated with ICI combination therapy were included. The median survival time (12.5 months vs 13.7 months, P = 0.285) and incidence of adverse events (P = 0.729) did not significantly differ between the PPI and non-PPI groups. Even after propensity score matching, the difference in median overall survival (OS) between the two groups was not significant (10.7 months vs 11.4 months; P = 0.596) and the patient’s OS is not significantly related to the dosage of PPI application (P > 0.05).However, according to our subgroup analysis, among HCC patients with a serum HBV DNA concentration ≥ 200 IU/mL, the use of PPIs significantly increased the risk of mortality in patients receiving ICI combination therapy (P = 0.024).Conclusion: PPIs do not notably influence the survival prognosis of patients receiving ICI combination therapy for HBV-associated advanced HCC. However, among patients with high levels of HBV DNA, PPIs increase the risk of mortality. Therefore, antiviral therapy should be intensified in the patients with HBVDNA > 200 IU/mL. Additionally, PPIs do not impact the incidence of adverse reactions in these patients.Keywords: hepatocellular carcinoma, immune checkpoint inhibitors, proton pump inhibitors, chronic hepatitis B virus infection